Top management team characteristics and firm growth: Evidence from a sample of listed companies. Issue 1 (2nd March 2015) - Colombelli, Alessandra
Abstract : Purpose: – The purpose of this paper is to identify the factors affecting the growth of companies listed on the Alternative Investment Market (AIM), the London Stock Exchange market for young and growing companies. Design/methodology/approach: – The author investigates post-initial public offering (IPO) growth for a panel of 665 companies listed on the AIM between 1995 and 2006. The empirical model uses the generalized method of moment-System (GMM-SYS) estimator. Findings: – The findings confirm that small companies listed on the AIM grow more quickly after the IPO. It seems that both human capital and firm characteristics are important determinants of their rapid growth. Practical implications: – The results of this study have some implications for policy. Policy makers should take account of the relevance of an efficient financial system. It is important also to consider the process of transformation of the cultural and behavioural attitudes of various countries towards entrepreneurship. Originality/value: – This paper analyses the determinants of firm growth in a particular entrepreneurial setting, that is, IPO on the AIM, the sub-market of the London Stock Exchange.